ANALISIS ANTIOKSIDAN, TOTAL FENOL DAN FISIKOKIMIA KOPI BRAND LOKAL ASAL BOGOR - Ria Atikah; Muhammad Fakih Kurniawan; Nursyawal Nacing (Universitas Muhammadiyah Semarang, 2023)
In Indonesia, local coffee brands very diverse and have different flavors and reliable in terms of aroma and taste based on raw materials from each region. This study aims to analyze antioxidant activity (IC50), total phenol and physicochemical local brand coffee from Bogor, Indonesia namely Cap Liong Bulan, Cap Oplet, Cap Teko and Cap Kacamata. the design used was a Completely Randomized Design (CRD) 1 factor. In the chemical test antioxidant activity of local Bogor brand coffee, the IC50 about 50,00 ppm and the total phenol test obtained values with a range of 0,70-2,25 mgGAE/g. Based on the pearson correlation test, the calculated r valeu of the relationship between total phenol and IC50 value was 0,880 > r table, so there is a correlation between total phenol and IC50. The result of pysicochemical test showed that the water content is around 1,5- 3,1%, ash content range from 2,3-4,8%, ph value ranges from 5,4-5,8, bulk density range from 0,4-0,5g/mL, total disolved solid range from 2,4-3,1Brix and coffee extract range from 23,7-28,0%. The result of the physical test carried out are in accordance with the maximum limit set by SNI.